Microbiological assessment of marine and estuarine ecosystems using fecal indicator bacteria, Salmonella, Vibrio and antibiotic resistance pattern. (July 2022) - Chahouri, Abir; Radouane, Nabil; Yacoubi, Bouchra; Moukrim, Abdellatif; Banaoui, Ali
Abstract: Marine and estuarine environments are often affected by microbiological contamination that adversely affects their use and severely impacts human health. To examine the influence of anthropogenic activities, this study used two different ecosystems in Agadir Bay, to compare fecal indicator bacteria (FIB) and bacterial pathogen profiles over two years. Vibrio target pathogens were detected at a high frequency (49.3%), while a low percentage (5.5%) was noted for Salmonella . Apart from those mentioned above, several other pathogenic bacteria were detected such as Cronobacter sakzakii, Pseudomonas fluorescens, and Aeromonas hydrophila. We also investigated the antimicrobial resistance of the pathogenic bacteria isolated. Salmonella strains were sensitive to all the antibiotics used, except ampicillin, amoxicillin + Ac clavulanic and chloramphenicol. And Vibrio strains were resistant to ampicillin, cephalothin, amikacin, and ciprofloxacin. This study highlights the limitations of FIB in assessing the microbiological quality and the importance of environmental surveys in understanding the distribution of pathogens. Graphical abstract: Unlabelled Image Highlights: Bivalves are the most effective tool for bacterial monitoring. FIB showed a significant correlation with Salmonella spp. and not with Vibrio spp. Bacteria isolates were sensitive to 6 of the 10 tested antimicrobials. Vibrio alginolyticus and Vibrio parahaemolyticus were the most widely isolated species. Salinity, conductivity and pH were the most correlated factors to bacterial contamination.